Flexible and Automatable Microfluidic-based Architecture and CAD Algorithm for Implementation of Large DNA Digital Storage - Pourasadollah, Mostafa; Taajobian, Maryam; Jahanian, Ali (2022 27th International Computer Conference, Computer Society of Iran (CSICC), 2022)
Demand for high-density and trusted digital data storage is growing dramatically such that current storage technologies cannot deliver enough space to satisfy the requirement. Recently, DNA storage showed an excellent potential to develop the need for high-density and long-lasting storage. However, DNA storage operations are manual currently, and they should be handled by humans, making numerous errors and wasting time. This paper proposed an architecture to provide an automated and parallel environment for storing and retrieving data using DNA storage and corresponding design algorithms using the digital microfluidic biochips (DMFB). We showed how this architecture could help in making parallel operations on DNA storage. We then demonstrate how our method can get scaled for more extensive DNA storage. Experimental results show that the proposed architecture can be used efficiently for large and complicated DNA storage systems.